Perancangan Aplikasi Sistem Pendukung Keputusan Penilaian Kinerja Karyawan Menggunakan Metode Moora - Gaol, Leliamas Lumban (STMIK Budi Darma, 2024)
Employee performance appraisal is an important process in effective human resource management. In the context of regional drinking water companies (PDAM), employee performance appraisal has a crucial role in ensuring optimal clean water services to the community. However, performance appraisals that are carried out manually and subjectively often face challenges and lack in providing accurate and fair results. However, in this article writers can present the use of the Multi Objective Optimization On The Basis Of Ratio Analysis (MOORA) method as an alternative approach in assessing the performance of PDAM employees. The MOORA method has proven effective in overcoming complex performance appraisal problems by integrating various relevant criteria and weights. So this method produces the highest alternative and the highest optimization value found in alternative A4 (Vendyco) with an optimization value of 0,293.